The Innovations Of The Islamic Civilization In The Fourth Century AH, And Their Role In The Progress Of European Civilization - Sameh Moustafa Al-Ashmawy (Elementary Education Online, 2023)
Abstract. Praise be to Allah Alim Fattah, creator of darkness and morning, reasoned guidance and righteousness, and destined distress and joy, and peace and blessings be upon our Prophet Mohammad Al-Bader, who loomed, light Wihdah, and his family and his people with justice and righteousness, civilization and science reform, Correct evidence, and jurisprudence facilitator available. It is not surprising that the Islamic civilization occupied the pages of history. Because of its many contributions in various fields. The Islamic civilization has a special flavor, and a distinctive personality that persisted over many centuries, and it still lives in our midst until now. There is no doubt that the search for Islamic civilization does not end with any limit. Because Islamic civilization is an open topic that cannot be closed, and the fields of research therein are wide spaces with extended horizons. Rather, research and studies on Islamic civilization are varied in the same way as curricula are renewed, methods develop, and intellectual, cultural, literary and artistic issues arise, which requires studying aspects of Islamic civilization in a new way. Therefore, I sought in this research characterized by (The innovations of the Islamic civilization in the fourth century AH, and their role in the progress of European civilization) to present the essence of Islamic civilization and its various innovations - especially - in the fourth century AH, which is considered the most brilliant era of Muslims, and to highlight the impact of Islamic civilization on European civilization. I divided it into two topics and a conclusion: So I devoted the first topic to talking about the aspects of Islamic civilization in the fourth century AH, where I presented a brief summary of the definition of civilization, then I spoke about the various aspects (organizations) of Islamic civilization, and I devoted the saying in some of the intellectual and intellectual sciences, such as: Qur’anic readings, modern jurisprudence schools, And the curricula of the hadiths in Q4 AH, linguistics, and astronomy, during the development of civilization during the fourth century AH.In the second topic, I explained the impact of the Arab-Islamic civilization on the European civilization, and in it I discussed the extent of the influence of the civilization of Islam on Europe, and in it I differentiated between the two civilizations - Islamic and European - and explained the methods of the arrival of Islamic civilization to Europe, and I cited evidence on the impact of Islam in some European countries, The effects of the Arab-Islamic civilization on the European civilization. In conclusion, I outlined the results of the research.